2015
DOI: 10.3892/or.2015.4387
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor promotes motility in breast cancer cells and disrupts non-transformed breast acinar structures

Abstract: A plethora of studies have demonstrated that chronic inflammatory microenvironment influences the genesis and progression of tumors. Such microenvironments are enriched with various lipid mediators. Platelet activating factor (PAF, 1-alkyl-2-acetyl-sn-glycero-3-phosphocholine) is one such lipid mediator that is secreted by different immune cell types during inflammation and by breast cancer cells upon stimulation with growth factors. Overexpression of PAF-receptor has also been observed in many other cancers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…On the other hand, JNK pathway inhibition resulted in inhibition of PAF stimulated enhanced motility as well as motility of unstimulated cells, confirming its role in PAF increased motility as well as inherent motility. Taken together, these results raise the possibility that PAF induced increased motility may be occurring through PI3K as well as JNK pathways [27] . Ongoing studies are being performed to dissect out the exact mechanistic pathway involved in PAF stimulated motility in cells.…”
Section: Research Highlightmentioning
confidence: 79%
See 3 more Smart Citations
“…On the other hand, JNK pathway inhibition resulted in inhibition of PAF stimulated enhanced motility as well as motility of unstimulated cells, confirming its role in PAF increased motility as well as inherent motility. Taken together, these results raise the possibility that PAF induced increased motility may be occurring through PI3K as well as JNK pathways [27] . Ongoing studies are being performed to dissect out the exact mechanistic pathway involved in PAF stimulated motility in cells.…”
Section: Research Highlightmentioning
confidence: 79%
“…In agreement with these reports we also observed increased collective cell migration of MDA-MB 231 cells upon PAF treatment in the wound healing assay. At the single cell level, PAF enhanced the velocity as well as distance traversed by the cells without change in directionality [27] . Further, to unravel the mechanistic aspect of PAF induced motility we used small molecule inhibitors of probable pathways predicted from available literature.…”
Section: Research Highlightmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated platelets create a procoagulant micro-environment that enables the tumor cells to cover themselves with platelets and evade the host immune system. Anandi VL et al demonstrated that platelet-activating factor promotes motility in breast cancer cells [ 24 ]. In addition, Toth B et al confirmed the key role of platelet-derived microparticles in the microenvironment of tumor tissue in breast cancer patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%